TREATMENT OUTCOMES OF PATIENTS WITH NEWLY DIAGNOSED ACUTE PROMYELOCYTIC LEUKEMIA; EXPERIENCE FROM A DEVELOPING COUNTRY - Javed, Hammad; Qamar Un Nisa Chudary,; Raheel Iftikhar,; Nighat Shahbaz,; Mehreen Ali,; Saima Hamayun, (Journal of Ayub Medical College Abbottabad, 2022)
Background: Acute promyelocytic leukaemia (APL) characterized by t (15;17) leading to formation of fusion protein PML-RARA is an acute leukaemia with highest mortality. A remarkable improvement in the outcomes has been witnessed due to evolution of highly effective targeted therapies replacing the traditional chemotherapy is most patients. However limited data is available regarding treatment outcomes of APL using various novel regimens from developing countries like Pakistan. Methods: This was a retrospective descriptive study which included APL patients treated at AFBMTC Rawalpindi from 2005 to 2020. It included a total of 51 eligible patients with a diagnosis of de novo APL confirmed by the presence of PML-RARA transcript or presence of t (15;17) by cytogenetics or FISH analysis. The protocols used for treatment included the UKAML MRC 12, the LPA-99/LPA-2005 PETHEMA, the APML4 and non-chemotherapy based ATO-ATRA protocol. Results: The study included 51 patients in which 31 (60.78%) were male and 20 (39.2%) were female. The median age at diagnosis was 30 years (range 5-70). The commonest symptom was fever seen in 43 (84.3%) patients and bruising was the commonest physical finding present in 44 (86.3%) patients. High-risk patients were 23 (46.1%), 18 (35.3%) were intermediate risk and 10 (19.6%) were low risk. The LPA99/LPA2005 was most frequently employed protocol being used in 36 (72%) patients. There were 2 deaths during induction and 44 (86.3%) achieved CR post induction. The median follow up time was 32 months (range 1 to 190 months) with an overall survival (OS) of 76.5% and a relapse free survival (RFS) of 66.7%. Conclusion: Our study shows APL is a highly curable malignancy and outcomes have improved with newer non-chemotherapy based therapies. It can also be concluded that outcomes of APL gradually improved over the past 2 decades due to improvement in supportive care, provision of blood products and use of newer protocols. The prognosis remains less favourable in high risk patients.